Is Childhood Abuse or Neglect Associated with Symptom Reports and Physiological Measures in Women with Irritable Bowel Syndrome? - Heitkemper, Margaret M. (2010)
PURPOSE: Early childhood traumatic experiences (e.g., abuse or neglect) may contribute to sleep disturbances as well as other indicators of arousal found in patients with irritable bowel syndrome (IBS). This study compared women with IBS positive for a history of childhood abuse and/or neglect to IBS women without this history, on daily gastrointestinal (GI), sleep, somatic, and psychological symptom distress, polysomnographic sleep, urine catecholamines and cortisol, and nocturnal heart rate variability (HRV). METHODS: Adult women with IBS recruited from the community were divided into 21 IBS with abuse/neglect and 19 IBS without abuse/neglect based on responses to the Childhood Trauma Questionnaire (physical, emotional, sexual abuse or neglect). Women were interviewed, maintained a 30-day symptom diary, and slept in a sleep laboratory. Polysomnographic and nocturnal heart rate variability data were obtained. First voided urine samples were assayed for cortisol and catecholamine levels. RESULTS: Women with IBS positive for abuse/neglect history were older than women without this history. Among GI symptoms, only heartburn and nausea were significantly higher in women with IBS with abuse/neglect. Sleep, somatic and psychological symptoms were significantly higher in women in the IBS with abuse/neglect group. With the exception of percent time in REM sleep, there were few differences in sleep stage variables and urine hormone levels. Mean heart rate interval and the Ln SDNN values were lower in those who experienced childhood abuse/neglect. CONCLUSION: Women with IBS who self report childhood abuse/neglect are more likely to report disturbed sleep, somatic symptoms, and psychological distress. Women with IBS should be screened for adverse childhood events including abuse/neglect.